A Strategic Synthesis Study of Artificial Intelligence Integration in Digital Marketing Systems Trends and Impacts on Organizational Performance - raungdessuwon, satchuset; ชัยมูล, วลัย (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This academic article aims to (1) synthesize trends in the application of artificial intelligence technology in digital marketing systems from international research, (2) analyze the empirical impacts of artificial intelligence on organizational effectiveness across various dimensions, including strategic planning, customer experience management, and competitive capability, and (3) develop a holistic strategic framework for Thai organizations in their digital transformation journey. The findings reveal significant trends in AI adoption that have expanded rapidly, particularly in personalized marketing, real-time big data analytics, and automated content management, which substantially enhance predictive decision-making capabilities and organizational strategic efficiency. The prominent impacts of AI on organizational performance encompass multiple dimensions: the financial dimension through improved forecasting accuracy, the customer dimension through enhanced experiences and loyalty, the process dimension through increased agility and cost reduction, and the learning and development dimension through the cultivation of data-driven and innovative organizational cultures. This research presents an AI-Driven Marketing Strategy Model, a conceptual framework that integrates technological, data, and human resource factors to support the systematic and sustainable implementation of AI in digital marketing systems for Thai organizations.